The PERAN KRITIS INFRASTRUKTUR MARITIM DALAM MANAJEMEN LOGISTIK PERTAHANAN INDONESIA MENUJU POROS MARITIM DUNIA - Afpriyanto, Afpriyanto; I Nengah Putra; Jupriyanto, Jupriyanto; Purnama Sari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Indonesia has ambitious goals to become a global maritime axis by harnessing its potential maritime resources. Maritime infrastructure and defense logistics management are crucial factors in achieving this objective. Strong maritime infrastructure supports defense logistics, troop mobility, and readiness in facing threats. As the largest archipelagic nation, Indonesia must overcome funding challenges and the complexity of maritime infrastructure development. Defense logistics management requires modern ports and efficient supply chains. Security challenges must also be addressed to safeguard strategic facilities and respond to threats. Maritime infrastructure also impacts economic growth. This study analyzes the role of maritime infrastructure in defense logistics management, identifies challenges, and considers the use of floating concrete as a solution. A Systematic Literature Review method is employed to gather literature. Challenges encompass geographical, financial, technical, regulatory, and environmental aspects. Strategies involving increased investment, long-term planning, coordination, security, and human resource development are needed. Floating concrete technology is proposed to strengthen maritime infrastructure and support the vision of a Global Maritime Axis. The success of defense logistics management and the maritime axis requires strategic collaboration and the implementation of appropriate solutions.